Comparative Analysis of In Vitro processivity of HIV-1 Reverse Transcriptases Containing Mutations 65R, 74V, 184V and 65R+74V - Sharma, Prem L. (2009)
While HIV-1 reverse transcriptase (RT) mutations of M to V at position 184 are commonly observed in the clinic, the double mutation of 65R+74V is rarely seen. It has been demonstrated that rapid R→K reversion occurs at RT codon 65 during replication of HIV-1 in human peripheral blood mononuclear cells containing 65R+74V mutations and that processivity of the RT is reduced relative to wild type. However, clinical studies show that M184V can be detected after several months of therapy interruption, suggesting more effective processivity. Herein, the in vitro RT processivity of genetically engineered M184V and double mutant 65R+74V was compared. Virion-associated RTs of WT pNL4-3, K65R, L74V, M184V and 65R+74V were used to perform RT processivity assays in the presence of trap, poly(rC)-oligo(dG). Both RTs with 184V and 65R+74V mutations exhibited similar processivity when compared with each other and a significantly decreased processivity as compared to WT RT. Both mutant RTs synthesized shorter cDNA molecules (37–42 nt) relative to WT RT, which made longer (65–70 nt) cDNA molecules. Since these surprising biochemical results cannot explain the clinical phenotype, a hypothesis is presented to explain the discrepancy and suggest new approaches for future testing.